Cross-Cultural Adaptation and Psychometric Evaluation of the Child and Adolescent Social Support Scale in Indonesian Adolescents - M. Ahkam Alwi; Ririn Mamiek Wulandari; Sigit Nugroho; Atikah Haira Bagawan (Universitas Ahmad Dahlan, 2026)
This study aimed to adapt and evaluate the psychometric properties of the Indonesian version of the Child and Adolescent Social Support Scale (CASSS) among high school students. Using a quantitative cross-sectional design, this study involved 320 students in Grades 10 and 11 in Surabaya, Indonesia. The adaptation process followed international test adaptation guidelines and included translation, synthesis, back-translation, expert review, and psychometric testing. Content validity was evaluated using the item-level content validity index, while construct validity was examined using confirmatory factor analysis. Internal consistency was assessed using Cronbach’s alpha and McDonald’s omega. The results showed excellent content validity, with all items achieving an I-CVI of 1.00. The five-factor model of the CASSS, consisting of support from parents, teachers, classmates, close friends, and people in school, demonstrated acceptable model fit: RMSEA = 0.055, CFI = 0.932, TLI = 0.925, GFI = 0.933, and SRMR = 0.057. Reliability coefficients were high across all subscales, with Cronbach’s alpha ranging from 0.921 to 0.967 and McDonald’s omega ranging from 0.866 to 0.953. The Parent subscale showed the highest mean score, indicating that parental support was the most prominent perceived source of support. These findings support the Indonesian CASSS as a valid and reliable instrument for assessing multidimensional perceived social support among Indonesian adolescents.